Multi-criteria analysis in modern information management - Dewri, Rinku, author; Whitley, L. Darrell, advisor; Ray, Indrajit, 1966-, advisor; Ray, Indrakshi, committee member; Siegel, Howard Jay, committee member (Colorado State University. Libraries, 2010)
The past few years have witnessed an overwhelming amount of research in the field of information security and privacy. An encouraging outcome of this research is the vast accumulation of theoretical models that help to capture the various threats that persistently hinder the best possible usage of today's powerful communication infrastructure. While theoretical models are essential to understanding the impact of any breakdown in the infrastructure, they are of limited application if the underlying business centric view is ignored. Information management in this context is the strategic management of the infrastructure, incorporating the knowledge about causes and consequences to arrive at the right balance between risk and profit. Modern information management systems are home to a vast repository of sensitive personal information. While these systems depend on quality data to boost the Quality of Service (QoS), they also run the risk of violating privacy regulations. The presence of network vulnerabilities also weaken these systems since security policies cannot always be enforced to prevent all forms of exploitation. This problem is more strongly grounded in the insufficient availability of resources, rather than the inability to predict zero-day attacks. System resources also impact the availability of access to information, which in itself is becoming more and more ubiquitous day by day. Information access times in such ubiquitous environments must be maintained within a specified QoS level. In short, modern information management must consider the mutual interactions between risks, resources and services to achieve wide scale acceptance. This dissertation explores these problems in the context of three important domains, namely disclosure control, security risk management and wireless data broadcasting. Research in these domains has been put together under the umbrella of multi-criteria decision making to signify that "business survival" is an equally important factor to consider while analyzing risks and providing solutions for their resolution. We emphasize that businesses are always bound by constraints in their effort to mitigate risks and therefore benefit the most from a framework that allows the exploration of solutions that abide by the constraints. Towards this end, we revisit the optimization problems being solved in these domains and argue that they oversee the underlying cost-benefit relationship. Our approach in this work is motivated by the inherent multi-objective nature of the problems. We propose formulations that help expose the cost-benefit relationship across the different objectives that must be met in these problems. Such an analysis provides a decision maker with the necessary information to make an informed decision on the impact of choosing a control measure over the business goals of an organization. The theories and tools necessary to perform this analysis are introduced to the community.
Department Head: L. Darrell Whitley.
Keywords: Information management; data broadcasting; multi-objective optimization; information security and privacy; Computer networks -- Security measures; Computer security; Multiple criteria decision making